Relationship between hepatitis C and kidney stone in US females: Results from the National Health and Nutrition Examination Survey in 2007–2018 - Chen, Yang; Shen, Xudong; Liang, Hu; Li, Guoxiang; Han, Kexing; Liang, Chaozhao; Hao, Zongyao (Frontiers in Public Health, 2022)
Background The main objective of this study is to explore the effects of hepatitis C (HCV) on the prevalence rate of kidney stones in US women. Method Dates for HCV infection and kidney stones were collected from National Health and Nutrition Examination Survey (NHANES) database, a cross-sectional study. The analysis samples included adults aged ≥20 years and women from six consecutive cycles of the NHANES 2007–2018. The association between HCV infection and kidney stones was performed by using logistic regression models. Subgroup analyses were conducted to find sensitive crowds. Results A total of 13,262 participants were enrolled, including 201 infected with HCV. After adjustment for potential confounders, we revealed a positive relationship between HCV and kidney stones (OR = 1.70, 95%CI:1.13–2.56). The crowds' statistically significant difference was characterized by other races (OR = 8.17, 95%CI:1.62–41.22) and BMI within 25–29.9 kg/m2 (OR = 2.45, 95%CI:1.24–4.83). Conclusions HCV infection may affect the prevalence of urolithiasis in US women, even the causal relationship remains unclear, the relation deserves special attention. We considered such a study an ideal way to begin exploring the effects of HCV on kidney stones.